2021
DOI: 10.1021/acssuschemeng.1c00253
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Development for 2,3-Butanediol Production from Crude Glycerol and Conceptual Process Design for Aqueous Conversion into Methyl Ethyl Ketone

Abstract: The transition to the circular economy era necessitates the sustainable production of chemicals using crude renewable resources via integrated biological and chemical conversion routes. Within this concept, this study combined experimental fermentation development with conceptual process design and technoeconomic evaluation to demonstrate the feasibility of bio-based methyl ethyl ketone (MEK) production from crude glycerol derived from industrial biodiesel production using soybean oil alone or mixed with tallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Many 2,3-BDO accumulating organisms, including bacteria and yeast strains, have been isolated and genetically engineered for high-level production. The microbes with the natural ability to accumulate 2,3-BDO can synthesize it from a variety of carbon sources, including sucrose, glucose, fructose, galactose, mannose, xylose, arabinose, and glycerol [10,24,31,35]. Table 2 summarises biosynthesis of 2,3-BDO from several pure substrates by various naturally producing bacterial strains and non-natural producer Saccharomyces cerevisiae.…”
Section: 3-bdo Accumulation From Pure and Crude Renewable Carbon Sourcesmentioning
confidence: 99%
“…Many 2,3-BDO accumulating organisms, including bacteria and yeast strains, have been isolated and genetically engineered for high-level production. The microbes with the natural ability to accumulate 2,3-BDO can synthesize it from a variety of carbon sources, including sucrose, glucose, fructose, galactose, mannose, xylose, arabinose, and glycerol [10,24,31,35]. Table 2 summarises biosynthesis of 2,3-BDO from several pure substrates by various naturally producing bacterial strains and non-natural producer Saccharomyces cerevisiae.…”
Section: 3-bdo Accumulation From Pure and Crude Renewable Carbon Sourcesmentioning
confidence: 99%
“…Acetoin was also synthesized from mixed sugar substrates and oil palm fiber or lignocellulosic hydrolysate, lactose, and bakery waste with a titer of up to 65.9 g L –1 . A more detailed overview on different microorganisms forming acetoin can be found in the literature. ,, These advances in substrate range, microbial productivity, and scalability of the fermentation process, paired with the promising results of Ochoa-Gómez et al utilizing model solutions, demonstrate the high potential of a sustainable production route for 2-butanone via acetoin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the acid-catalyzed dehydration of 2,3-BD to 2butanone in an aqueous environment has been investigated. 30 While the study showed promising results, the catalytic reaction was modeled, based on model solution experiments. 31 A different route to produce 2-butanone has been presented in 1984: In a two-stage process, 2,3-BD was first electrochemically oxidized to acetoin, which was subsequently reduced to 2-butanone.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing manufacturing of biofuels, glycerol is produced in large quantities as the unavoidable byproduct of biodiesel production. Converting the excess glycerol into high-value chemicals like l -serine is necessary for the sustainability of the biofuel economy. In the present study, we designed an artificial enzymatic reaction cascade for conversion of glycerol into l -serine (Figure A). Glycerol was first oxidized into d -glycerate by alditol oxidase from Streptomyces coelicolor A3 (ScALDO).…”
Section: Introductionmentioning
confidence: 99%